Effects of Brassica oleraceae Leaves on Serum Liver Function of Wistar Rats Intoxicated with Prednisolone - Amen, Ananias; Yusufu, Dawoye; Oladele, Gloria Omonefe; Umaru, Kerenhappuch Isaac (African Journal of Sciences and Traditional Medicine, 2024)
The recent study investigated the effects of ethanol extract of Brassica oleracaeae leaves on prednisolone induced toxicity in male albino rats. Liver markers were assayed in order to investigate the toxic effect of prednisolone and the ameliorating effects of the extract. Sixteen (16) rats grouped in to four (n=4) were administered prednisolone and ethanol leaves extract based on the experimental design. The male albino rats were sacrificed after the experimental period of fourteen (14) days, blood was collected for assay of the liver function by ocular puncture. Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT) levels were significantly (p<0.05) increased from 5.67 ± 5.13 and 6.67 ±7.02 to 26.67 ± 8.02 and 25.00 ± 4.00 respectively when rats where administered with prednisolone toxicity. Upon treatment of rats with ethanol leaves extract of B. oleraceae at 100mg/kg, the concentration of AST and ALT were lowered to 7.67 ± 6.81 and 8.00 ± 7.55 respectively. A further increased in the concentration of the extract to 300mg/kg resulted to a significant (p<0.05) increased of AST (9.33 ± 8.12) and ALT (12.00 ± 10.00) levels. Similarly, the levels of alkaline phosphatase (ALP) and Albumin increases in the group that were administered with prednisolone however, when rats were treated with ethanol leaves extract of Brassica oleracaeae such concentrations were decreased. The findings of this study can be concluded that, the ethanol leaves extract of Brassica oleracaeae showed capacity in ameliorating the effects induced by prednisolone intoxication.